Human rights : a very short introduction - Clapham, Andrew (Oxford University Press, 2007)
Today it is usually not long before a problem gets expressed as a human rights issue. An appeal to human rights in the face of injustice can be a heartfelt and morally justified demand for some, while for others it remains merely an empty slogan. Taking an international perspective and focusing on highly topical issues such as torture, arbitrary detention, privacy, health and discrimination, this Very Short Introduction will help readers to understand for themselves the controversies and complexities behind this vitally relevant issue. Looking at the philosophical justification for rights, the historical origins of human rights and how they are formed in law, Andrew Clapham explains what our human rights actually are, what they might be, and where the human rights movement is heading. ABOUT THE SERIES: The Very Short Introductions series from Oxford University Press contains hundreds of titles in almost every subject area. These pocket-sized books are the perfect way to get ahead in a new subject quickly. Our expert authors combine facts, analysis, perspective, new ideas, and enthusiasm to make interesting and challenging topics highly readable.